Repeated Administration of Cigarette Smoke Condensate Increases Glutamate Levels and Behavioral Sensitization - Ryu, In Soo; Kim, Jieun; Seo, Su Yeon; Yang, Ju Hwan; Oh, Jeong Hwan; Lee, Dong Kun; Cho, Hyun-Wook; Lee, Kyuhong; Yoon, Seong Shoon; Seo, Joung-Wook; Shim, Insop; Choe, Eun Sang (Frontiers in Behavioral Neuroscience, 2018)
Nicotine, a nicotinic acetylcholine receptor agonist, produces the reinforcing effects of tobacco dependence by potentiating dopaminergic and glutamatergic neurotransmission. Non-nicotine alkaloids in tobacco also contribute to dependence by activating the cholinergic system. However, glutamatergic neurotransmission in the dorsal striatum associated with behavioral changes in response to cigarette smoking has not been investigated. In this study, the authors investigated alterations in glutamate levels in the rat dorsal striatum related to behavioral alterations after repeated administration of cigarette smoke condensate (CSC) using the real-time glutamate biosensing and an open-field behavioral assessment. Repeated administration of CSC including 0.4 mg nicotine (1.0 mL/kg/day, subcutaenous) for 14 days significantly increased extracellular glutamate concentrations more than repeated nicotine administration. In parallel with the hyperactivation of glutamate levels, repeated administration of CSC-evoked prolonged hypersensitization of psychomotor activity, including locomotor and rearing activities. These findings suggest that the CSC-induced psychomotor activities are closely associated with the elevation of glutamate concentrations in the rat dorsal striatum.